THE IMPLEMENTATION OF SIMON SAYS GAME TO IMPROVE STUDENTS’ VOCABULARY MASTERY IN LEARNING ENGLISH AT MTS. LABORATORIUM UIN -SU MEDAN - Muhammad Dalimunthe (UIN Sumatera Utara, 2018)
This research was aimed to improve the students’ vocabulary mastery in learning English by using Simon says game. The subject of this research was seventh grade at MTs Laboratorium UIN-SU Medan in 2017 academic year. This research of this study was conducted by using classroom action research . The data used in this research were quantitative and qualitative data and the instruments of collecting data were used such as: Pre-test and Post-test, interview sheet, observation sheet, and photography evidence. The result of this research showed that there was increasing of students’ vocabulary mastery. The mean of the pre- test was 44.75, in cycle one was 64.5, in cycle two was 80.5, it indicated that the scores and the mean in cycle twowere better than the first one. The percentage of students who got point 70 or more also increased. In the pre-test, there were not students who got point 70. In the post-test of cycle one the students who got point 70 or more there were 23 of students (57.5%). It means that there was an increasing about 57.5%. The post-test of cycle two, the students who got point 70 or more there were 34 students (85%) and the increasing was about 27.5%. For the hypothesis testing used t-tes formula. It could be seen that coefficient of t count (16.19) with fact level = 0.05 was 3.558 in the coefficient of t count (16.19) > table (3.558). Thus, alternative hypothesis (Ha) stated that Simon says game could improve the students’ vocabulary mastery accepted. The score of observation sheet were 4 (very good), and the students were happy to learn vocabulary by using Simon says game it could be seen in the result of interview and photography evidence. It showed that the class rooms were alive and active.Keywords: Simon says game, Students’ vocabulary mastery